A vinheta de abertura da Copa FIFA de 2014 : produto de espetacularização ou referencial de identidade cultural? - Guimarães, Ivana Auxiliadora Gonçalves (2018)
This dissertation intends to analyze the elements of Brazilian cultural / national identity present in the research object - Opening Voucher of the 2014 FIFA World Cup. The general proposal was to understand to what extent this production contributed to a possible reinforcement to the references of culture and identity or whether the production was only a development of the spectacular process of sport. Therefore, it was sought to understand if there is the influence of the media in the diffusion and / or solidification of such cultural / national elements, besides presenting other conceptions and ideas that were discovered in the exercise of data analysis. To that end, some authors and concepts were used as theoretical bases in this work: Clifford Geertz's concept of culture, Stuart Hall's identity, Benedict Anderson's notion of imagined communities, Gilberto Freyre's interpretations of Brazil, Roberto Damatta, José Carlos Reis, besides the notions of mercantilization and spectacularization of the sport, present in Pierre Bourdieu and other authors. This research, regarding the objective, consisted of a qualitative analysis, that counted on the application of personal interviews, through the instrument of collection known as test of association of words. In general terms, the respondent was invited to relate words, after contact with what is called an inducer stimulus (in this case, the vignette). Regarding the results achieved, it is worth noting the sheer size and emotional impact of the production in the subjects interviewed. However, the analysis shows that there is no central commitment of the entity that promotes the event with the diffusion or maintenance of the national identities of the host country, but with the sporting spectacle and its logic.